Chronic limb-threatening ischemia under the age of 50 – a single-center 12-year retrospective study - Inês Gueifão; Anita Quintas; Rita Soares Ferreira; Fábio Pais; Tiago Ribeiro; Joana Cardoso; Helena Fidalgo; Maria Emília Ferreira (Angiologia e Cirurgia Vascular)
INTRODUCTION: Premature peripheral artery disease (PAD), defined as occurring before or at the age of 50, is a poorly studied subset of PAD due to its low incidence. It has been associated with a higher risk of progression to chronic limb-threatening ischemia (CLTI), major adverse limb events and mortality. Etiology is multifactorial, with genetics and environmental causes at play, with the most common risk factors being smoking, diabetes, and hypertension.